Surface Modification Techniques to Produce Micro/Nano-scale Topographies on Ti-Based Implant Surfaces for Improved Osseointegration - Hou, Chuang; An, Jing; Zhao, Duoyi; Ma, Xiao; Zhang, Weilin; Zhao, Wei; Wu, Meng; Zhang, Zhiyu; Yuan, Fusheng (Frontiers in Bioengineering and Biotechnology, 2022)
Titanium and titanium alloys are used as artificial bone substitutes due to the good mechanical properties and biocompatibility, and are widely applied in the treatment of bone defects in clinic. However, Pure titanium has stress shielding effect on bone, and the effect of titanium-based materials on promoting bone healing is not significant. To solve this problem, several studies have proposed that the surface of titanium-based implants can be modified to generate micro or nano structures and improve mechanical properties, which will have positive effects on bone healing. This article reviews the application and characteristics of several titanium processing methods, and explores the effects of different technologies on the surface characteristics, mechanical properties, cell behavior and osseointegration. The future research prospects in this field and the characteristics of ideal titanium-based implants are proposed.